Analysis and experiment of blank holder gap in the cylindrical cup deep drawing of low carbon steel to prevent cracking-wrinkling / Susila Candra and Hudiyo Firmanto - Candra, Susila; Firmanto, Hudiyo (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
This paper aims to investigate Blank Holder Gap (BHG) in order to prevent wrinkles and crack defects in the deep drawing process of cylindrical cups with a diameter of 30 mm, using low carbon steel grade SPCC that is 0.7 mm thick. Mathematical and experimental approaches were applied to study the effect of BHG on wrinkle wave height and product quality. The analytical approaches used were the slab method and the Forming Limit Diagram (FLD) to determine the final thickness of the product specimen and the height of the wrinkling wave, respectively. Each method in this study had been compared to each other. Punch-die dimensions were determined based on the standard tool designed. According to the research, BHG is set 100% to 114% of the thickness of the initial material or equivalent about 0.70 to 0.80 mm. By using the value of this gap, the height of wrinkles can be avoided, the magnitude of the drawing force is still below the critical limit, and the product specimen does not experience wrinkles and cracks. The results of this study are applicable to the deep drawing of cup products on SPCC material with a thickness of no more than 1 mm.